2017
DOI: 10.1007/s11892-017-0848-5
|View full text |Cite
|
Sign up to set email alerts
|

T-cell Metabolism as a Target to Control Autoreactive T Cells in β-Cell Autoimmunity

Abstract: Purpose of reviewAn increasing body of evidence indicates that bio-energetic metabolism of activated T cells is a potential target to control the autoimmune response in type 1 diabetes (T1D).Recent findingsT-cell activation and proliferation is linked to the cell capacity to provide sufficient energy and biosynthesis molecules to support T-cell growth and division. This makes T cells susceptible to metabolic inhibition for the control of the T-cell response. There is a wide therapeutic arsenal of metabolic inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…With respect to potential side effects of GLUT1 inhibition in humans, studies of the GLUT1 deficiency syndrome reported mild to severe neurological disorders in infants and children affected, whereas in adult life, most symptoms were stable or diminished (37). Since overexpression of GLUT1 is not limited to autoreactive T cells and metabolism is increased in activated T cells, we can envisage a strategy in which adult patients undergoing islet transplantation have a selective reactivation of autoreactive T-cell clones (38). This model provides the opportunity for using WZB117 for a limited time period and increasing the selectivity of the treatment for activated autoreactive T cells that upregulate glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to potential side effects of GLUT1 inhibition in humans, studies of the GLUT1 deficiency syndrome reported mild to severe neurological disorders in infants and children affected, whereas in adult life, most symptoms were stable or diminished (37). Since overexpression of GLUT1 is not limited to autoreactive T cells and metabolism is increased in activated T cells, we can envisage a strategy in which adult patients undergoing islet transplantation have a selective reactivation of autoreactive T-cell clones (38). This model provides the opportunity for using WZB117 for a limited time period and increasing the selectivity of the treatment for activated autoreactive T cells that upregulate glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Because the metabolism of T lymphocytes is so closely linked to their activation, differentiation, and survival, there is tremendous interest in manipulating metabolic processes for therapeutic purposes. This topic has been well reviewed recently ( 112 115 ) so only a brief summary of potential lipid metabolic drug targets will be described here. It is likely that many existing drugs used to normalize metabolic imbalances might be “repositioned” for use in other indications including treatment of autoimmunity and graft-versus-host disease (GVHD).…”
Section: A Role For Lipid Metabolism In T-cell Subset Differentiationmentioning
confidence: 99%
“…Importantly, adaptive memory responses are also very well known to play a crucial part in autoimmune diseases. However, the role of the adaptive immune system in these diseases has been discussed elsewhere in very good recent review articles ( 19 21 ) and was therefore not included in this review.…”
Section: Introductionmentioning
confidence: 99%